Pengembangan Kurikulum Pendidikan Islam di Era New Normal - Ossi Marga Ramadhan; Acep Heris Hermawan; Mohamad Erihadiana (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
This study intends to analyze the Islamic education curriculum development in the New Normal era, using a qualitative approach to library research. Researchers found that what must pursue the Islamic education curriculum in the New Normal period by integrating content, preparing a systematic learning concept and good training in terms of the use of technology so that it is accustomed to carrying out the learning process online. One of the ideal educational strategies during this pandemic is to explore the government's provisions by using an agreed application. There are two crucial component elements in the implementation of the learning process activities; namely, students and educators must be given training related to technology media to know the direction of learning so that they avoid mistakes that will become a problem. Meanwhile, students carry out learning at home with the help of parents who supervise every activity during the online learning process so that learning misunderstandings do not occur during a pandemic.